Avaliação das propriedades mecânicas de aço bifásico e sua análise metalográfica - Gomes, Pedro Meirelles Chagas Delfino [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Due to the need of utilizing high strength steels, the automobile industry started researching the advanced high strength steels (AHSS) and their multiphase microstructure, being the DP (Dual Phase) steel one of the first ones. Several methods were studied regarding the microstructure of the materials in order to obtain better mechanical properties. Within this scenario, the present work has two main objectives: first, to evaluate the mechanical properties of two DP steels through the tensile test, one with ultimate tensile strength (UTS) 1000 MPa and the other with 1200 MPa, furthermore one will calculate the anisotropy of both materials. Second, one will analyze the multiphase microstructure of both materials through the metallography test. From the tensile test one will determine several parameters such as: ultimate tensile strength (UTS), yield strength (YS), young modulus, resilience modulus, ductility, amongst others. The microscopic analysis of the microstructure allows us to distinguish the present phases in the material. The microstructure revealed that the DP steels are composed of one phase of martensite, responsible for the high strength, and one of ferrite, responsible for the high elongation (and low yield point.) Based on the tensile strength test one can infer that the value of the properties obtained in the experimental method matches the previous expectation, indicating that the steel is recommended for its proposal. The anisotropy revealed that both steels are not suitable for stamping, due to the fact that their normal anisotropy index are way low comparing to other normal indices literature values. Yet, the DP1000 will tend to bend the metal sheet in the edges, creating 'earings' during the metal forming process, because of it planar anisotropy index

Devido a necessidade da indústria automobilística em utilizar aços com alta resistência mecânica (maior que 500 MPa) e satisfatório elongamento (maior que 20%) os aços avançados com suas microestruturas multifásica encontraram seu espaço, sendo o DP (Dual Phase ou bifásico) um dos pioneiros nessa empreitada. Diversos métodos foram estudados a fim de mudar a microestrutura do material com objetivo de obter melhores propriedades mecânicas. Dentro desse cenário, o presente trabalho tem dois objetivos, primeiro avaliar as propriedades mecânicas de dois tipos de aços avançados Dual Phase (DP) através do ensaio de tração, com tensão última a tração de 1000 MPa e 1200 MPa, e também calcular a anisotropia desses materiais. Além disso, será analisado a microestrutura multifásica dos dois materiais através do ensaio de metalografia. A partir do ensaio de tração determinar-se-á parâmetros como: limite de resistência a tração (LRT), limite de escoamento, módulo de elasticidade, ductilidade, entre outros. A partir da análise microscópica da microestrutura determinar-se-á as fases constituintes de ambos os aços, qualitativamente. A análise microscópica revelou que os aços DP são constituídos de martensita, responsável pela parte da alta resistência mecânica do material, e ferrita, responsável pela parte de alto elongamento do material. A partir do ensaio de tração observa-se que os valores das propriedades obtidos experimentalmente com os ensaios conferem com os dados esperados teoricamente. A anisotropia revelou que ambos aços não são adequados estampagem, visto que seus valores de anisotropia normal são muito baixos. Ainda, no aço DP 1000, haverá a tendência de formar 'orelhas' nas chapas durante o processo de conformação, devido ao seu índice de anisotropia planar
Evaluation of the mechanical properties of biphasic steel and its metallographic analysis
Keywords: Aço de alta resistência; Metalografia; Anisotropia; Steel, High strength